Foreign direct investment and education as determinants of environmental quality: The importance of post Paris Agreement (COP21). (15th September 2020) - Zafar, Muhammad Wasif; Qin, Quande; malik, Muhammad Nasir; Zaidi, Syed Anees Haider
Abstract: This study investigates the effect of foreign direct investment and education on environmental quality for Asian countries by controlling income, energy consumption, and urbanization for the period of 1990–2018. We have applied panel cointegration techniques to probe for long-run associations among the variables. The empirical results indicate the existence of cointegration between the variables. Dynamic ordinary least square and fully modified least square methods are applied to estimate long-run elasticities. The empirical results confirm that environmental quality is sensitive to foreign direct investment, education, and urbanization. Income and energy consumption deteriorate environmental quality by increasing CO2 emissions. In the long-run, bidirectional causal associations are found for emissions- foreign direct investment, emissions-energy use, income- emissions, foreign direct investment -income, and energy-income nexus. Furthermore, there is a unidirectional causality running from education and urbanization to emissions, foreign direct investment, income, and energy use. Policymakers in Asian economies are encouraged to establish policies that increase the education budget, promote the use of green energy, attract foreign direct investment with green technology, and expand cities to limit the urbanization effects on environmental quality. Highlights: This paper investigates the linear and nonlinear impact of FDI and education on carbon emissions. FMOLS and VECM are employed in Asian countries. FDI and education increase carbon emissions in Asian countries. Energy consumption and economic growth stimulate the level of carbon emissions. Results indicate the existence of EKC for FDI, education, and income.